Regime Shifts in Glacier and Ice Sheet Response to Climate Change: Examples From the Northern Hemisphere - Marshall, Shawn J. (Frontiers in Climate, 2021)
Glaciers and ice sheets are experiencing dramatic changes in response to recent climate change. This is true in both mountain and polar regions, where the extreme sensitivity of the cryosphere to warming temperatures may be exacerbated by amplification of global climate change. For glaciers and ice sheets, this sensitivity is due to a number of nonlinear and threshold processes within glacier mass balance and glacier dynamics. Some of this is simply tied to the freezing point of water; snow and ice are no longer viable above 0C, so a gradual warming that crosses this threshold triggers the onset of melting or gives rise to an abrupt regime shift between snowfall and rainfall. Other nonlinear, temperature-dependent processes are more subtle, such as the evolution from polythermal to temperate ice, which supports faster ice flow, a shift from meltwater retention to runoff in temperate or ice-rich (i.e., heavily melt-affected) firn, and transitions from sublimation to melting under warmer and more humid atmospheric conditions. As melt seasons lengthen, there is also a longer snow-free season and an expansion of glacier ablation area, with the increased exposure of low-albedo ice nonlinearly increasing melt rates and meltwater runoff. This can be accentuated by increased concentration of particulate matter associated with algal activity, dust loading from adjacent deglaciated terrain, and deposition of impurities from industrial and wildfire activity. The loss of ice and darkening of glaciers represent an effective transition from white to grey in the world’s mountain regions. This article discusses these transitions and regime shifts in the context of challenges to model and project glacier and ice sheet response to climate change.